Evaluation of influence of male hormonal therapy on self estimation of patients health condition - Mroczkowski, Artur; Wdowiak, Artur; Bakalczuk, Grzegorz; Jakiel, Grzegorz; Bakalczuk, Szymon (Menopause Review/Przegląd Menopauzalny, 2002)
In Poland 4.3 mln males are over fifty. In aging males along with beginning of andropause, their health condition is getting worse, what can show in subjective feeling and in objective decreasing of some of organism well being indexes. It become a very important for medicine to help men during andropause. Aim of this study was explaining if replacement hormonal therapy except actual supplementation of male hormone shortage, can also improve patients frame of mind and what goes after this improve life quality in subjective indexes. The study was performed by using questionnaire between 38 men, age from 45 to 65 with andropausal symptoms. The patients were under supervision of Department of Reproduction and Andrology University School of Medicine in Lublin during 2000 and 2001. Twenty randomly chosen men made examined group, who were taking one of testosterone drug during period of 18 months. Control group was created of 18 men who did not take hormonal replacement therapy. It was ascertained that men who were taking hormonal replacement therapy evaluated their health condition on higher level in comparison to men who did not. It was shown that self estimation of health condition is connected with males educational level.